2022
DOI: 10.1101/gad.348782.121
|View full text |Cite
|
Sign up to set email alerts
|

Highly rigid H3.1/H3.2–H3K9me3 domains set a barrier for cell fate reprogramming in trophoblast stem cells

Abstract: The placenta is a highly evolved, specialized organ in mammals. It differs from other organs in that it functions only for fetal maintenance during gestation. Therefore, there must be intrinsic mechanisms that guarantee its unique functions. To address this question, we comprehensively analyzed epigenomic features of mouse trophoblast stem cells (TSCs). Our genome-wide, high-throughput analyses revealed that the TSC genome contains large-scale (>1-Mb) rigid heterochromatin architectures with a high degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…2a,b and Extended Data Fig. 3a–c ) 47 . Similarly, Polycomb-regulated genes remained predominantly within A compartments, indicating that these regions retain topological features of euchromatin despite elevated DNA methylation levels (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…2a,b and Extended Data Fig. 3a–c ) 47 . Similarly, Polycomb-regulated genes remained predominantly within A compartments, indicating that these regions retain topological features of euchromatin despite elevated DNA methylation levels (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…47 In addition, trophoblast cell-specific large heterochromatin architecture with a high degree of histone H3.1/3.2 and H3K9me3 accumulation (THDs) are found in both species. 48 However, there are clear differences related to gene regulation networks between mice and humans as follows. First, Cdx2 is progressively restricted to the outer cells in the morula.…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
“…Specifically, tissue‐dependent and differentially methylated regions between trophoblast and embryonic lineages are conserved between them 47 . In addition, trophoblast cell‐specific large heterochromatin architecture with a high degree of histone H3.1/3.2 and H3K9me3 accumulation (THDs) are found in both species 48 …”
Section: Mouse Placentamentioning
confidence: 99%
“…It should be noted that specific aberrations in epigenetic patterns can be found in preimplantation embryos, preceding SCNT-associated abnormal phenotypes such as death of embryos during the postimplantation period (Matoba et al, 2011;Gao et al, 2018). Indeed, a recent study demonstrated that transient Xist upregulation, induced by loss of maternal polycomb PRC2, in the preimplantation period could show a detrimental ripple effect resulting in postimplantation death in mice (Matoba et al, 2022). Therefore, it is important to identify other SCNT-specific changes in the epigenome or gene expression patterns during preimplantation development for further technical improvements of SCNT technology.…”
Section: Introductionmentioning
confidence: 99%
“…Because the imprinting memory of Xist has been erased in somatic cells including trophoblasts ( Oikawa et al, 2014 ; Inoue et al, 2017 ), Xist is ectopically expressed in SCNT-derived preimplantation embryos, leading to a large-scale suppression of X-linked genes in such embryos. The third significant step for the improvement of mouse SCNT was activation of the donor cell-derived H3K9me3-enriched regions containing genes specifically repressed in SCNT-derived embryos (termed “reprogramming resistant regions”, RRRs) by a specific histone demethylase, Kdm4d ( Matoba et al, 2014 ; Hada et al, 2022 ). More recently, we and others have confirmed that loss of H3K27me3-dependent imprinting (noncanonical imprinting) inherited from the donor somatic cells was the major cause of SCNT-specific placental enlargement ( Matoba et al, 2018 ; Inoue et al, 2020 ; Wang et al, 2020 ; Xie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%